Acceptability and effectiveness of antimicrobial stewardship implementation strategies on fluoroquinolone prescribing. (12th November 2021) - Suda, Katie J.; Clore, Gosia S.; Evans, Charlesnika T.; Reisinger, Heather Schacht; Kale, Ibuola; Echevarria, Kelly; Sherlock, Stacey Hockett; Perencevich, Eli N.; Goetz, Matthew Bidwell
Abstract: Objective: To assess the effectiveness and acceptability of antimicrobial stewardship-focused implementation strategies on inpatient fluoroquinolones. Methods: Stewardship champions at 15 hospitals were surveyed regarding the use and acceptability of strategies to improve fluoroquinolone prescribing. Antibiotic days of therapy (DOT) per 1, 000 days present (DP) for sites with and without prospective audit and feedback (PAF) and/or prior approval were compared. Results: Among all of the sites, 60% had PAF or prior approval implemented for fluoroquinolones. Compared to sites using neither strategy (64.2 ± 34.4 DOT/DP), fluoroquinolone prescribing rates were lower for sites that employed PAF and/or prior approval (35.5 ± 9.8; P = .03) and decreased from 2017 to 2018 ( P < .001). This decrease occurred without an increase in advanced-generation cephalosporins. Total antibiotic rates were 13% lower for sites with PAF and/or prior approval, but this difference did not reach statistical significance ( P = .20). Sites reporting that PAF and/or prior approval were "completely" accepted had lower fluoroquinolone rates than sites where it was "moderately" accepted (34.2 ± 5.7 vs 48.7 ± 4.5; P < .01). Sites reported that clinical pathways and/or local guidelines (93%), prior approval (93%), and order forms (80%) "would" or "may" be effective in improving fluoroquinolone use. Although most sites (73%) indicated that requiring infectious disease consults would or may be effective in improving fluoroquinolones, 87% perceived implementation to be difficult. Conclusions: PAF and prior approval implementation strategies focused on fluoroquinolones were associated with significantly lower fluoroquinolone prescribing rates and nonsignificant decreases in total antibiotic use, suggesting limited evidence for class substitution. The association of acceptability of strategies with lower rates highlights the importance of culture. These results may indicate increased acceptability of implementation strategies and/or sensitivity to FDA warnings.